PROGRAM EXCELLENCE SOLUTION UNTUK MENURUNKAN WAKTU PENGERJAAN REMANUFACTURING UNIT KOMATSU PC2000-8 DI PT UT SITE KALIMANTAN SELATAN - Vuko A.T. Manurung; Lukyawan Pama Deprian; Yohanes Tri Joko Wibowo (President University, 2019)
With the passage of time the heavy equipment unit will experience a decrease. In order to return the unit to its initial performance, the Reman manufacturing process is abbreviated as Reman. Reman is an activity carried out to keep heavy equipment units close to performance when first created.PT UT site Adaro is trusted by its customers to do Reman specifically for Komatsu PC 2000-8 type excavators. In the implementation there was a delay in the implementation of the work process to 80 days. Therefore, a program was created to reduce the total leadtime to 45 days or down by 44%.